1971
DOI: 10.1084/jem.133.6.1377
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunity in Vitro

Abstract: The relationship between classical delayed hypersensitivity, as exemplified by the tuberculin-type skin test, and cellular immunity, here defined as an acquired enhancement of resistance to infection with intracellular microorganisms, has long been a subject of investigation. Recently the delayed hypersensitivity reaction has been opened to renewed study because in vitro models such as lymphocyte transformation and macrophage migration inhibitory factor (MIF) 1 production have been developed (1). The work of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(18 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…The events underlying this activation process have not been determined, but they could involve the activity of a lymphokine. In fact, it has been reported recently that a product of antigen-stimulated lymphocytes can influence the microbicidal capacity of macrophages in vitro (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The events underlying this activation process have not been determined, but they could involve the activity of a lymphokine. In fact, it has been reported recently that a product of antigen-stimulated lymphocytes can influence the microbicidal capacity of macrophages in vitro (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphokineinduced alterations in the behavior of these cells may play an important role in inflammation and cell-mediated immune reactions (19). The enhancement of bactericidal activity against intracellular parasites has been described as one of the important functional properties of macrophages associated with the acquisition of cell-mediated immunity (14,19) and a lymphokine, the macrophage activating factor (MAF), is thought to enhance their bactericidal activity. Little is known, however, about the mechanism(s) by which lymphokines interact with target cells.…”
mentioning
confidence: 99%
“…Therefore, identity of antigenicity between eliciting antigens and target bacteria may not be required. Reports that cellular resistance to Listeriamonocytogenes can be transferred by BCG-immune lymphoid cells, but its induction requires injection of an eliciting dose of BCG into the recipients [19], and that intracellular growth of L. monocytogenes was inhibited under the influence of BGG-immune lymphoid cells and BGG [9,[26][27][28] seem to support the concept that macrophages are nonspecifically activated to become bactericidal by sensitized lymphocytes stimulated with specific antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Simon and Sheagren recently showed that macrophages from immune peritoneal exudate cells cultivated with specific antigen before infection had markedly enhanced listericidal activity, but supernatants from stimulated lymphocytes with specific antigen exhibited only substantial migration inhibitory-factor activity but did not enhance the listericidal activity of macrophages [26][27][28]. However, it has to be confirmed whether such correlation between immune lymphoid cells and nonspecific bactericidal activity of macrophages is true or not in the case of M. tuberculosis since the growth rate of tubercle bacilli is much slower than that of Listeria.…”
mentioning
confidence: 99%